A novel double quad-inverter configuration for multilevel twelve-phase open-winding converter - Padmanaban, Sanjeevikumar; Blaabjerg, Frede; Wheeler, Patrick; Ojo Olorunfemi, Joseph; Maroti, Pandav Kiran (2016)
This paper work articulates the novel proposal of double quad-inverter configuration for multilevel twelve-phase open-winding ac converter. Modular power units are developed from reconfigured eight classical three-phase voltage source inverters (VSIs). Each VSI has one additional bi-directional switching device (MOSFET/IGBT) per each phase and linked neutral with two capacitors. An original modified single carrier five-level modulation (MSCFM) algorithm is developed and modulates each 2-level VSIs as equivalent to ones 5-level multilevel inverter. Observed set of results are presented with model based numerical simulation software’s (Matlab/PLECS) developments. Further, the results confirm the good agreement to the developed theoretical background. Proposed converter suits the need of low-voltage/high-current applications such as ac tractions and ‘More-Electric Aircraft’ propulsion systems